Combination Of Aroma Therapy And P6 (Nei Guan) Point Acupressure On Emesis Gravidarum In Primipara - Sutrisna Altahira (Jurnal EduHealth, 2023)
Nausea and vomiting occur in 60-80% of primigravidas and 40-60% occur in multigravidas (Mahdika, 2016). Nausea and vomiting in pregnant women if not treated immediately will result in a very weak mother's body, pale face and decreased frequency of urination so that body fluids decrease and blood becomes thick (hemoconcentration). This study aims to determine the effectiveness of the combination of aromatherapy and acupressure at point P6 (Nei Guan) for emesis gravidarum at the Waara Health Center, Muna Regency. The design of this study used the Pretest-Posttest with control design. The study design used pre- and post-tests in the intervention group (pregnant women with emesis gravidarum who were given a combination of aromatherapy and acupressure at point P6) in the control group (pregnant women with emesis gravidarum who were given acupressure at point P6). The bivariate test obtained a value of 0.001, namely α> 0.05 so that Ha was accepted, namely there was an effect of giving a combination of point P6 acupressure with Lemon aromatherapy on emesis gravidarum in primiparous women.